Yerevan 1924: master plan - Bagina, Elena; Arustamyan , Margarita (project baikal, 2020)
The master plan of Yerevan created in 1924 by Alexander Tamanyan and Nikolay Buniatyan is a reflection of the military-political situation prevailing in Armenia after the First World War, the genocide of 1915, the revolutions in Turkey and Russia, the social illusions of the Armenian diaspora and political parties that set out to create an independent Republic of Armenia as a center for the preservation of Armenian culture. The change in the “client” of this project and the political plans did not affect the idea of a “garden city” and the planning principles laid down by Tamanyan. The activities of the Armenian Assistance Committee made it possible to realize the ideas of the master plan.
Keywords: Alexander Tamanyan; Nikolay Buanityan; 1924 Master Plan of Yerevan; garden city; capital; Armenian Assistance Committee (AAC)